2015
DOI: 10.1016/j.circir.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor metastásico de colisión. Informe de un caso

Abstract: The presence of collision tumours is extremely rare. There are no statistics or specific treatment reported. Diagnosis is made with histopathology. At the moment, no similiar cases have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The histopathological study reported bilateral ovary adenocarcinoma, as well as metastatic collision tumor of two histological types: well differentiated adenocarcinoma and a mixed malignant mesodermic Müllerian tumor. The patient was treated with adjuvant chemotherapy with poor results (death in 24 months) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological study reported bilateral ovary adenocarcinoma, as well as metastatic collision tumor of two histological types: well differentiated adenocarcinoma and a mixed malignant mesodermic Müllerian tumor. The patient was treated with adjuvant chemotherapy with poor results (death in 24 months) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%